UPAYA MENINGKATKAN KEMAMPUAN MERANGKAI GERAK DASAR TARI BALI MELALUI PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA SISWA KELAS X.A SMAN 3 DENPASAR (Widyadari, 2024)
The basic movements of Balinese dance are broadly divided into three parts, namely agem, Tandang, and Tangkep. However, there are still many students who cannot do the basic dance movements well. The aim of this research is to improve student learning outcomes in the material of assembling basic Balinese dance movements by applying a learning model. Project Based Learning and to find the difficulties faced by students in the material of composing basic Balinese dance movements by applying the Project Based Learning learning model. This research was carried out in two cycles, where each cycle included the stages of planning, implementation, observation or observation as well as analysis and reflection. The data analysis technique that will be used in this research is quantitative data analysis. The research results show an increase in each cycle. In the pre-cycle, the average student score was very low with a poor prediction of 59.4. In the implementation of cycle I, the student's score increased with a sufficient predicate, namely 74.85. In cycle II there was an increase which was able to meet the KKM value with a very good prediction, namely 82.98. The difficulties faced by students in learning to compose the basic movements of Balinese dance are their lack of understanding and comprehension of the basic movements which are the main elements in a dance and also their fear of practicing the basic movements of Balinese dance.